Confucianism and American philosophy - Foust, Mathew A. (Albany, NY : SUNY, Press, 2017)
A comparative analysis of Confucianism and the American Transcendentalist and Pragmatist traditions. In this highly original work, Mathew A. Foust breaks new ground in comparative studies through his exploration of the connections between Confucianism and the American Transcendentalist and Pragmatist movements. In his examination of a broad range of philosophers, including Confucius, Mencius, Xunzi, Ralph Waldo Emerson, Henry David Thoreau, Charles Peirce, William James, and Josiah Royce, Foust traces direct lines of influence from early translations of Confucian texts and brings to light conceptual affinities that have been previously overlooked. Combining resources from both traditions, Confucianism and American Philosophy offers fresh insights into contemporary problems and exemplifies the potential of cross-cultural dialogue in an increasingly pluralistic world.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Philosophy, Confucian -- China; Confucianism -- China; Philosophy, American; Philosophie confucéenne -- Chine; Confucianisme -- Chine; Philosophie américaine.; PHILOSOPHY / Movements / Pragmatism; Confucianism; Philosophy, American; Philosophy, Confucian; China